Advances in biotechnology and informatics to link variation in the genome to phenotypes in plants and animals - Appels, R. (Springer-Verlag, 2013)
Advances in our understanding of genome structure provide consistent evidence for the existence of a core genome representing species classically defined by phenotype, as well as conditionally dispensable components of the genome that shows extensive variation between individuals of a given species. Generally, conservation of phenotypic features between species reflects conserved features of the genome; however, this is evidently not necessarily always the case as demonstrated by the analysis of the tunicate chordate Oikopleura dioica. In both plants and animals, the methylation activity of DNA and histones continues to present new variables for modifying (eventually) the phenotype of an organism and provides for structural variation that builds on the point mutations, rearrangements, indels, and amplification of retrotransposable elements traditionally considered. The translation of the advances in the structure/function analysis of the genome to industry is facilitated through the capture of research outputs in “toolboxes” that remain accessible in the public domain.